MENATA AKAL DALAM TAFSIR BI AL-RA’YI: DARI OTORITAS ILMU HINGGA BATAS PENYIMPANGAN - Ranya Fariha Nasaruddin; Rahmi Damis; Muhammad Irham (STAI Dirosat Islamiyah Al-Hikmah Jakarta, 2026)
This article explores the dynamics of tafs?r bi al-ra’yi as a Qur’anic hermeneutical approach that integrates rational capacity (?aql) within a rigorous epistemological framework of tafsir. The study aims to elaborate the fundamental concept of tafs?r bi al-ra’yi, to distinguish its classification into commendable (mamd??a) and blameworthy (ma?m?m) forms, and to map the methodological prerequisites required for its proper application. Employing a qualitative-descriptive research design based on library research, this study synthesizes data from authoritative primary sources and supporting literature within the disciplines of Qur’anic studies and u??l al-fiqh. The findings affirm that tafs?r bi al-ra’yi does not represent a liberalized, purely subjective mode of interpretation, but rather constitutes a legitimate form of ijtihad when conducted in accordance with Arabic linguistic principles, Shar??ah norms, and the contextual framework of revelation. This article underscores the urgency of regulating the authority of reason in Qur’anic interpretation to ensure scholarly validity while preserving the authenticity of the divine message.